Nilai-Nilai Kepemimpinan Sando Batu dalam Pelaksanaan Masara di Desa Compong Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Barisan Barisan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
This research’s objective was to determine the leadership values of ​​Sando Batu in Masara Ritual at Compong Village of Pitu Riase Sub District in Sidenreng Rappang Regency. Public perception of the applied leadership of Sando Batu was considered unique, because Sando Batu as the leader did not seem to talk much and give orders but played a significant role in people's lives. The methods used to collect data were (1) observation, (2) questionnaire, (3) interviews, and (4) library research. The collected data were then analyzed using frequency data. Population in this study were 150 people, all of them were accounted as sample. The results showed that the leadership value of ​​Sando Batu in Masara Ritual was a percentage of 70,5% as high. The affecting factors were the role of Sando Batu as the Lumika’s community leader which scored a percentage of 76,22%, and Masara being an obligation for every citizen of Lumika’ with a percentage of 71,67%.